Efeito de distintas entradas de ar em aviários de alta densidade para a produção de frangos de corte - Costa, Crislaine da (2011)
The experiment was conducted in negative pressure poultry houses, with the same supply of equipment, management and construction, located in the southwestern region of Paraná, in the city of Quedas do Iguaçú, between the months of September and October 2011. This study aims to evaluate the effect of different air intakes on the poultry house environment and the surface temperature of broilers reared in negative pressure poultry houses. The experiment was divided into three treatments: T1 = open air intake, T2 = air intake with ceramic, T3 = air intake with cellulose material. The birds used in the experiment were of the same lineage and were housed at a density of 18 birds / m². To assess the effect of air intakes in the environment we analyzed the following variables: surface temperature of the environment, surface temperature of the air intakes and birds. These variables were recorded by means of a thermographic camera (Flir Systems). To this end, data were collected weekly from the first week-old birds, at 12:00 pm, with three replications. Data were analyzed by ANOVA and comparison of means by Tukey test (P ≤ 0.05), using the software Excel. The poultry houses equipped with evaporative cellulose panels had the lowest average surface temperatures of birds and the internal environment, thus favoring the thermal comfort of broilers. Moreover, both the HVAC systems uniformly controlled environment inside the poultry houses.